Characterization and Identification of Chemical Functional Groups in Oyster Mushroom (Pleurotus Ostreatus) Broth added with Vegetables and Spices - Siti Maulyda Ayu MZ; Halifah Pagarra; Irma Suryani Idris Langi'; Oslan Jumadi; Hartati (Bionature, 2023)
Adding the nutritional content of broth powder without destroying the distinctive taste of the broth can be doneusing pure mushroom extract and additional vegetables and spices. This study aims to determine the organolepticcharacteristics and identify the chemical functional groups of glutamic acid in the best samples of oyster mushroombroth powder added with vegetables and spices. The results of the organoleptic test were tabulated in a table andthen analyzed using a descriptive test. The organoleptic characteristics of the best color parameters were intreatment B1 which had a pale white color. The best treatment of aroma, texture, and taste parameters were foundin the B2 treatment with a characteristic aroma of typical broth, fine powder texture, and has a distinctive taste ofbroth. The identification of the functional groups of secondary metabolites using the Fourier Transform Infrared(FTIR) instrumentation. Identification results with FTIR showed absorption at wave number (cm-1): 3419.74,2934.62, 1639.56, 1409.70, 1055.55. There is N-H, O-H, C-H, C=O carbonyl group and carboxylic C-O, whichidentify the presence of amide compound, phenol acid, alkane, aldehydes, amid I and carboxylic acid, which areknown as glutamic acid in this sample.